Laser powder bed fusion of a new high gamma prime Ni-based superalloy with improved weldability. (October 2021) - Jena, Ashutosh; Atabay, Sila Ece; Gontcharov, Alexandre; Lowden, Paul; Brochu, Mathieu
Graphical abstract: Highlights: Crack-free LW 4275 with a strong <100> was fabricated by laser powder bed fusion. Suitable heat-treatment cycle was determined by Thermo-Calc modeling. Heat-treament resulted a bimodal distribution of gamma prime precipitates. Good combination of mechanical properties was observed in heat-treated LW 4275. Abstract: This study reports the crack-free fabrication of a new high gamma prime precipitation hardened Ni-based superalloy by Laser Powder Bed Fusion (LPBF) process. In the as-built condition, scanning electron microscopy and electron backscattered diffraction analysis indicated the presence of elongated columnar grains with an orientation along 〈1 0 0〉 direction. Following the sub-solvus heat treatment cycle determined using Thermo-Calc software, crack-free microstructure with columnar grains was observed along 〈1 0 0〉 orientation. High-resolution scanning electron microscope analysis revealed a bimodal distribution of gamma prime precipitates and a uniform distribution of carbide precipitates in the heat-treated samples. As a result of heat treatment, hardness increased from 365 HV to 508 HV. The heat-treated samples also displayed excellent yield strength, ultimate tensile strength, and elongation of 939 MPa, 1368 MPa, and 23% respectively at room temperature. Mechanical testing at elevated temperatures confirmed the yield strength, tensile strength, and elongation reached 80 MPa, 106 MPa, and 34% respectively at 1121 °C. The stress rupture test of the heat-treated samples revealed good creep properties with rupture times of 559 h and 75 h, respectively, at 927 °C and 982 °C, for stresses of 152 MPa and 138 MPa.